2014
DOI: 10.1590/bjpt-rbf.2014.0061
|View full text |Cite
|
Sign up to set email alerts
|

Static body postural misalignment in individuals with temporomandibular disorders: a systematic review

Abstract: BACKGROUND: The association between body postural changes and temporomandibular disorders (TMD) has been widely discussed in the literature, however, there is little evidence to support this association. OBJECTIVES: The aim of the present study was to conduct a systematic review to assess the evidence concerning the association between static body postural misalignment and TMD. METHOD: A search was conducted in the PubMed/Medline, Embase, Lilacs, Scielo, Cochrane, and Scopus databases including studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
(223 reference statements)
0
23
0
14
Order By: Relevance
“…The severity of TMD is an important finding to evaluate the progression and impact of dysfunction in the life of the affected individuals 15,18 . However, to the best of our knowledge, the design of studies involving TMD and body posture generally only associates postural conditions with the presence of dysfunction [6][7][8]12 and it does not seek to investigate this relationship with TMD severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of TMD is an important finding to evaluate the progression and impact of dysfunction in the life of the affected individuals 15,18 . However, to the best of our knowledge, the design of studies involving TMD and body posture generally only associates postural conditions with the presence of dysfunction [6][7][8]12 and it does not seek to investigate this relationship with TMD severity.…”
Section: Discussionmentioning
confidence: 99%
“…Milanesi et al 10 observed that the higher the anterior position of the head, the greater the severity of signs and symptoms related to mandibular movements and masticatory muscles. In the review by Chaves et al 7 , of the 20 articles that investigated the craniocervical posture, ten found postural changes of this segment in the TMD group. Among these ten, three found lower anterior head angles related to the presence of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically postural compensations are expected in adjant segments, considering that muscle chains are interconnected22 ) . Power et al studied the effects of PA mobilization on lumbar segments and reported that PA spinal mobilization consistently produced lumbar extension18, 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Chaiane Facco Piccin (1) Daniela Pozzebon (1) Laís Chiodelli (1) Jalusa Boufleus (1) Fernanda Pasinato (1) Eliane Castilhos Rodrigues Corrêa (1) …”
Section: Aspectos Clínicos E Psicossociais Avaliados Por Critérios Deunclassified
“…Temporomandibular disorder (TMD) is a term used to designate several clinical signs and symptoms affecting the muscles of mastication, the temporomandibular joint (TMJ) and structures associated 1,2 . It is considered as a multifactorial disorder 3,4 , presenting as its etiologic factors joint trauma, occlusal discrepancies, joint hypermobility, skeletal problems, parafunctional habits, and psychosocial and behavioral factors 5 .…”
Section: Introductionmentioning
confidence: 99%